Total knee arthroplasty and medial patellofemoral ligament reconstruction for knee osteoarthritis with habitual patellar dislocation: a case report - Zhou, Hanyu; Zhu, Hongguang; Lv, Duanbo; Liu, Qiaolin; Zheng, Yinghao; Lin, Facai; Li, Jian; Xing, Zhenlong (Frontiers in Surgery, 2025)
BackgroundKnee osteoarthritis and habitual patellar dislocation are clinically common osteoarticular diseases. However, existing literature lacks reports on their co-occurrence and treatment approaches. Thus, we propose a surgical approach that integrates total knee arthroplasty with medial patellofemoral ligament reconstruction, addressing knee osteoarthritis alongside habitual patellar dislocation.Case presentationA 78-year-old female developed habitual lateral patellar dislocation of the left knee after an accidental fall over 20 years ago. One year prior, she experienced weight-bearing pain in the left knee. Physical examination, full-length lower limb radiography, and computed tomography confirmed a diagnosis of left knee osteoarthritis with habitual patellar dislocation. The patient subsequently underwent total knee arthroplasty combined with medial patellofemoral ligament reconstruction.ConclusionThis case demonstrates notable innovation among similar reports. It may represents an effective treatment, enabling the patient to walk without impediment, with a stable and pain-free knee joint and no significant patellar displacement during flexion. Further case studies are still required to validate the generalizability of this surgical technique.